Effect of Storage Period Fertile Chicken Egg in Refrigerator on Mortality Rate, and Hatchability Rate - Chaovapasee, Kanok; Nakdaeng, Nirandorn (Princess of Naradhiwas University Journal, 2021)
The objective of this research was to study the effect of storage period in refrigerator on mortality rate and hatchability rate of fertile chicken egg. The experiment was distributed in completely randomized design (CRD) with 3 treatments (egg storage 1 to 7 days, egg storage 8 to 14 days, and egg storage 15 to 21 days, respectively). Each treatment contained 8 replicates with 14 eggs per replication. The results shown that the effect of egg storage periods did not significant on early embryonic death (1 to 7 days after incubate), middle embryonic death (8 to 18 days after incubate), hatchability rate, late embryonic death (19 to 21 days after incubate), and piped (p>0.05). Therefore, this study indicated that small animal farmers could store fertile egg in refrigerator temperature for 3 weeks but the high number of piped might be found in this condition.